2009
DOI: 10.1111/j.1540-6040.2009.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

The Simultaneous Effect of Social Distance and Physical Distance on the Formation of Neighborhood Ties

Abstract: Prior studies have separately suggested the importance of physical distance or social distance effects for the creation of neighborhood ties. This project adopts a case study approach and simultaneously tests for propinquity and homophily effects on neighborhood ties by employing a full‐network sample from a recently developed New Urbanist neighborhood within a mid‐sized southern city. The authors find that physical distance reduces the likelihood of weak or strong ties forming, suggesting the importance of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
124
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(140 citation statements)
references
References 80 publications
8
124
0
2
Order By: Relevance
“…For example, the presumption that there will be social ties spanning racial/ethnic groups is questionable, as studies have found that there are fewer social ties in general in such neighborhoods (Lowenkamp, Cullen, and Pratt 2003;Warner and Rountree 1997), less neighborhood attachment (Sampson 1991), and less neighborhood satisfaction (Hipp 2009;Sampson 1991). Given the consistent evidence that neighborhoods with higher levels of racial/ethnic heterogeneity have higher levels of crime (Hipp 2007;Roncek and Maier 1991;Rountree and Warner 1999;Sampson and Groves 1989), this provides additional evidence that such neighborhoods may not always exhibit economic vibrancy as expected.…”
Section: How Mixing Might Hinder Neighborhood Dynamismmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, the presumption that there will be social ties spanning racial/ethnic groups is questionable, as studies have found that there are fewer social ties in general in such neighborhoods (Lowenkamp, Cullen, and Pratt 2003;Warner and Rountree 1997), less neighborhood attachment (Sampson 1991), and less neighborhood satisfaction (Hipp 2009;Sampson 1991). Given the consistent evidence that neighborhoods with higher levels of racial/ethnic heterogeneity have higher levels of crime (Hipp 2007;Roncek and Maier 1991;Rountree and Warner 1999;Sampson and Groves 1989), this provides additional evidence that such neighborhoods may not always exhibit economic vibrancy as expected.…”
Section: How Mixing Might Hinder Neighborhood Dynamismmentioning
confidence: 90%
“…Carolina also found that income differences reduced the probability of forming a social tie, even controlling for the spatial distance between housing units (Hipp and Perrin 2009). And the evidence that mixed income neighborhoods tend to have higher levels of crime also calls into question the presumption that they will have long-term beneficial consequences (Hipp 2007;Hipp and Boessen 2013;Messner and Tardiff 1986).…”
Section: How Mixing Might Hinder Neighborhood Dynamismmentioning
confidence: 99%
“…Egy kapcsolat lét-rejötte kevésbé valószínű, illetve nagyobb erőfeszítést igényel, ha a két fél közötti távol-ság növekszik (Borgatti et al 2009, Perrin 2009. A kapcsolatok fenntartásának leghaté-konyabb módja a személyes találkozás, amelyet a távolság nagyban akadályoz (Granovetter 1973).…”
Section: Bevezetésunclassified
“…Both studies acquired data on telephone and e-mail use, and though both recognised the importance of physical distance to the strength of social interactions, Hipp and Perrin (2009) did not report any relationship between technology use and distance, and Mok et al (2010) found technology use to be insensitive to distance. This prior work stands in contrast to the distance-dependent behaviours identified in the second level of Figure 7 that defined Groups I-IV discussed in the previous section.…”
mentioning
confidence: 99%
“…Distance does appear as a consideration in more recent work on social networks, with Hipp and Perrin (2009) seeking an empirical base for equivalence between physical distance and social distance, and Mok et al (2010) exploring the impact of the internet on interpersonal contact. Both studies acquired data on telephone and e-mail use, and though both recognised the importance of physical distance to the strength of social interactions, Hipp and Perrin (2009) did not report any relationship between technology use and distance, and Mok et al (2010) found technology use to be insensitive to distance.…”
mentioning
confidence: 99%